The Impact of Sustainable Development Goal Adoption on Corporate Financial Performance : Empirical Analysis of European Publicly Listed Companies 2019 - 2023 - Larkomaa, Emil (My University, 2024)
The relationship between Sustainable Development Goals (SDGs) and corporate financial performance (CFP) has garnered increasing interest in recent years, particularly as sustainability initiatives become integral to business strategy. The results of this study contribute to the growing body of literature suggesting that companies adopting and reporting on Environmental, Social, and Governance (ESG) factors may experience enhanced financial performance. Corporate sustainability is increasingly recognized as a critical element of modern business strategy. As firms face growing pressure from stakeholders, regulators, and investors to integrate ESG considerations into their operations, the pursuit of sustainability has become both a business imperative and a societal responsibility. While there are still some issues concerning how sustainability is measured and how much companies should focus on the immediate financial results while pursuing long-term objectives, the majority of studies indicate that sustainable companies can generate higher financial performance. This study demonstrates a positive correlation between the SDGs reported by European companies and key financial metrics such as market-adjusted returns (MAR), total stock return (Total Return), price-to-earnings ratio (P/E), and earnings per share (EPS) by using regression models. A portfolio analysis provides further insights into the financial benefits of SDG reporting in terms of historical returns. Two portfolios were constructed based on high and positive SDG reporting characteristics, and their cumulative returns between 2019 and 2023 were compared to the STOXX Europe 600 index. The analysis found that the portfolio consisting of specific positively contributing SDGs outperformed both the high SDG count portfolio and the market index while retaining similar levels of riskiness. The broader implications of these findings point to the value of sustainability in corporate strategy. Companies actively engaging with SDGs, particularly those aligned with social and environmental impact, tend to see more favorable financial outcomes. This aligns with previous studies, which have shown that firms incorporating sustainability efforts, such as SDG initiatives, tend to outperform those that do not. The portfolios that outperformed the market index reinforce the idea that SDG engagement is beneficial for social and environmental reasons and financial gain.

Suhde kestävän kehityksen tavoitteiden (SDG) ja yritysten taloudellisen suorituskyvyn (CFP) välillä on herättänyt kasvavaa kiinnostusta viime vuosina, erityisesti kun kestävyysaloitteet ovat tulleet kiinteäksi osaksi liiketoimintastrategiaa. Tämän tutkimuksen on tarkoitus osoittaa, että ympäristö-, sosiaali- ja hallintotekijöiden (ESG) käyttöönotto ja raportointi voi parantaa yritysten taloudellista suorituskykyä. Yritysten kestävyys nähdään yhä enemmän keskeisenä osana nykyaikaista liiketoimintastrategiaa. Kun yrityksiin kohdistuu yhä suurempia paineita sidosryhmiltä, sääntelyviranomaisilta ja sijoittajilta vastuullisuustavoitteiden sisällyttämiseksi toimintaansa, kestävyydestä on tullut sekä liiketoiminnallinen välttämättömyys että yhteiskunnallinen vastuu. Vaikka haasteita on edelleen kestävyyden mittaamisessa ja lyhyen aikavälin taloudellisen suorituskyvyn tasapainottamisessa pitkän aikavälin tavoitteiden kanssa, on vahvaa näyttöä siitä, että kestävyyttä edistävät yritykset voivat saavuttaa pitkällä aikavälillä parempia tuloksia. Tässä tutkimuksessa osoitetaan regressioanalyysin ja portfolioanalyysin avulla positiivinen yhteys eurooppalaisten yritysten raportoimien SDG:iden määrän ja tyypin sekä keskeisten taloudellisten mittareiden, kuten markkinakorjatun tuoton (MAR), kokonaisosaketuoton (Total Return), P/E-luvun ja osakekohtaisen tuloksen (EPS), välillä. Potfolioanalyysi tarjoaa lisäymmärrystä SDG-raportoinnin taloudellisista hyödyistä. Kaksi salkkua rakennettiin perustuen korkeisiin ja positiivisiin SDG-raportointiominaisuuksiin, ja niiden kumulatiivisia tuottoja vuosien 2019–2023 välillä verrattiin STOXX Europe 600 -indeksiin. Analyysi osoitti, että salkku, joka koostui erityisistä positiivisesti vaikuttavista SDG:istä, ylitti sekä korkean SDG-määrän salkun että markkinaindeksin tuotot samalla, kun riskitasot pysyivät samanlaisina. Näiden löydösten laajemmat vaikutukset korostavat kestävyyden arvoa yritysstrategiassa. Yritykset, jotka aktiivisesti sitoutuvat SDG-tavoitteisiin, erityisesti sosiaalista ja ympäristövaikutusta edistäviin, näyttävät saavuttavan suotuisampia taloudellisia tuloksia. Tämä tukee aiempia tutkimuksia, jotka ovat osoittaneet, että kestävyyspyrkimyksiä, kuten SDG-aloitteita, toteuttavat yritykset pärjäävät keskimääräistä paremmin. Salkut, jotka ylittivät markkinaindeksin tuotot, vahvistavat ajatusta siitä, että SDG-tavoitteiden edistäminen ei ole hyödyllistä pelkästään sosiaalisista ja ympäristösyistä, vaan myös taloudellisen hyödyn näkökulmasta.
Keywords: UN Sustainable Development Goals, Corporate Social Responsibility, Corporate Financial Performance, YK:n kestävän kehityksen tavoitteet, yritysvastuu, yritysten taloudellinen suorituskyky